Clinical Significance and Prognostic Value of Human Soluble Resistance-Related Calcium-Binding Protein: A Pan-Cancer Analysis - Zhang, Jinguo; Chen, Jian; Shan, Benjie; Lin, Lin; Dong, Jie; Sun, Qingqing; Zhou, Qiong; Han, Xinghua (Frontiers in Medicine, 2021)
Soluble resistance related calcium binding protein (Sorcin, SRI) serves as calcium-binding protein for regulation of calcium homeostasis and multidrug resistance. Although mounting evidence suggests a crucial role of SRI in chemotherapeutic resistance of certain types of tumor, insights into pan-cancer analysis of SRI are unavailable. Therefore, we aimed to probe the multifaceted properties of SRI across 33 cancer types. SRI expression was analyzed via The Cancer Genome Atlas (TCGA) and Genotype Tissue-Expression (GTEX) database. SRI genomic alterations and drug sensitivity analysis were performed based on the cBioPortal and CellMiner database. Furthermore, the correlations between SRI expression and survival outcomes, clinical features, stemness, tumor mutation burden (TMB), microsatellite instability (MSI) and immune cells infiltration were analyzed using TCGA data. The differential analysis showed that SRI was upregulated in 25 tumour types compared to normal tissues. Aberrant expression of SRI was able to predict survival in different cancers. Further, the most frequent alteration of SRI genomic was amplification. Moreover, the aberrant SRI expression was related to stemness score, EMT-related genes, MSI, TMB and tumor immune microenvironment in various types of cancer. TIMER database mining further found that SRI expression was significantly correlated with the infiltration levels of various immune cells in certain types of cancer. Intriguingly, SRI expression was negatively correlated with drug sensitivity of fluorouracil, paclitaxel, docetaxel, and isotretinoin. Our findings highlight the predictive value of SRI in cancer and provide insights for illustrating the role of SRI in tumorigenesis and drug resistance.